Kemudahan Penggunaan, Tingkat Keberhasilan Transaksi, Kemampuan Sistem Teknologi, Kepercayaan dan Minat Bertransaksi Menggunakan Mobile Banking - I Gusti Bagus Putra Adiwijaya (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe purpose of this study is to determine the effect of ease of use, the success rate of transactions, and the ability of technology systems to trust and to determine the effect of ease of use, the success rate of transactions, the ability of technology systems and interest in transactions using mobile banking. This research was conducted at PT. Bank Rakyat Indonesia (BRI) Branch Gatot Subroto Denpasar. Data collection techniques used questionnaires to 160 Bank BRI customers selected as samples. Data were analyzed with Structural Equation Modeling (SEM) with AMOS program. Ease of use, transaction success rate, and technological system capability have a positive and significant impact on trust and interest in transactions using mobile banking. This means that the better ease of use, the success rate of transactions, and the ability of technology systems, the higher the customer confidence and impact on the increasing interest in transactions using mobile banking.